Gift Giving at Israeli Weddings as a Function of Genetic Relatedness and Kinship Certainty. Issue 1 (1st December 2017) - Tifferet, Sigal; Saad, Gad; Meiri, Mali; Ido, Nir
Abstract : This study examines gift giving at Israeli weddings. In accordance with kin selection theory, we hypothesized that wedding guests possessing greater genetic relatedness to the newlyweds would offer greater sums of money as wedding gifts. We also hypothesized that family members stemming from the maternal side (where the genetic lineage has higher kinship certainty) would offer the newlyweds more money than those stemming from the paternal side. Data on the monetary gift sums of the wedding guests from 30 weddings were collapsed according to two criteria: (a) genetic relatedness (0%, 6.25%, 12.5%, 25%, and 50%) and (b) kinship certainty (maternal or paternal lineage). Both hypotheses were supported. We discuss the implications of these data in understanding family dynamics, as well as practical applications associated with the marketing of gifts.